Five strategic foresight tools to enhance business model innovation teaching - Matthew J. Spaniol; Christina M. Bidmon; Anna Holm; René Rohrbeck (Journal of Business Models, 2019)
We discuss our lessons from 8 years of teaching business model innovation to executives in our part-time MBA program. We inspect how the usage of 5 strategic foresight tools has supported students to innovate business models and discuss the advantages and disadvantages of using student-owned live cases.